2009
DOI: 10.1002/14651858.cd007424.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging versus computed tomography for detection of acute vascular lesions in patients presenting with stroke symptoms

Abstract: DWI appears to be more sensitive than CT for the early detection of ischaemic stroke in highly selected patients. However, the variability in the quality of included studies and the presence of spectrum and incorporation biases render the reliability and generalisability of observed results questionable. Further well-designed studies without methodological biases, in more representative patient samples, with practicality and cost estimates are now needed to determine which patients should undergo MRI and which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(56 citation statements)
references
References 115 publications
3
51
0
2
Order By: Relevance
“…A diffusion-weighted imaging MRI protocol has been shown to discriminated stroke mimics from arterial strokes. [23][24][25] At our hospital the facilities did not at the time of the study allow rapid examination with MRI. The decrease in DTN times in recent years may also lead to higher frequencies of stroke mimics receiving thrombolysis, as could be shown in a single centre study that found an association between decreasing DTN times and increased frequencies of stroke mimics receiving IVT.…”
Section: Multivariate Analysis Of Predictors Of Stroke Mimicsmentioning
confidence: 99%
“…A diffusion-weighted imaging MRI protocol has been shown to discriminated stroke mimics from arterial strokes. [23][24][25] At our hospital the facilities did not at the time of the study allow rapid examination with MRI. The decrease in DTN times in recent years may also lead to higher frequencies of stroke mimics receiving thrombolysis, as could be shown in a single centre study that found an association between decreasing DTN times and increased frequencies of stroke mimics receiving IVT.…”
Section: Multivariate Analysis Of Predictors Of Stroke Mimicsmentioning
confidence: 99%
“…In our study cerebral computer tomography was used far more often to image subarachnoid hemorrhage than MR. According to a review by Brazelli et al CT and MRI are equal in detecting acute vascular lesions in patients presenting with stroke symptoms [14]. Computer tomography has some advantages such as being less costly, quicker to perform and easier to tolerate [14].…”
Section: Discussionmentioning
confidence: 99%
“…48, 50, 5359 In anterior circulation strokes, the DWI lesion volume correlates well with baseline clinical stroke severity, final infarct volume, and clinical outcome (Level II). 6062 Although strong evidence suggests that MRI is superior to NCCT for confirming stroke within the first 24 hours (Level 1a) 53 , logistical issues related to performing MRI in the emergent setting, as well as the proven benefit of CT-based selection in randomized controlled trials, limit the use of MRI in the emergent setting (Table 3). Therefore, MRI may be reserved for select patients in whom the clinical diagnosis is uncertain or for centers that have MRI readily available 24/7 with streamlined protocols in order to limit imaging time within the standard-of-care guidelines for thrombolytic therapy.…”
Section: Rationale and Imaging Evidence For Acute Ischemic Stroke Patmentioning
confidence: 97%
“…4853 Its sensitivity in detecting ischemia is reported as 99% with a high specificity of 92%. 48, 50, 5359 In anterior circulation strokes, the DWI lesion volume correlates well with baseline clinical stroke severity, final infarct volume, and clinical outcome (Level II).…”
Section: Rationale and Imaging Evidence For Acute Ischemic Stroke Patmentioning
confidence: 99%
See 1 more Smart Citation